THE PRECARIOUSNESS OF EMPLOYMENT LINKS FOR NURSES IN MUNICIPALITIES IN NORTHERN MINAS GERAIS - Janice Drumond Morais, Ariadna; Ribeiro de Souza Silva, Sueli; Drumond Carvalho Morais, Victória; Henrique Neves Borborema, Gustavo (Health and Society, 2025)
Objective: To evaluate the employment bond of the nurses of the Family Health Strategies of the north of Minas Gerais regarding the stability offered to this professional. Method: Quantitative research carried out in database - CNES - National Register of Health Establishments. The studied population was composed of 679 nurses working in the municipalities of the North of Minas Gerais in the public health units registered in the CNES.Establishments). Results: Most of the bonds offered to these professionals are precarious links. Fixed-term employment contracts do not guarantee stability and bring as a consequence the break in the link between professional and population and the discontinuation of care. These precarious links in the Family Health Strategy are fragile and subject the worker to political instability and are not able to guarantee the labor rights of nurses. Conclusion: Part of the municipalities in the north of Minas Gerais does not follow the Federal Constitution that determines the access to the public service by the competition. The instability of a bond directly interferes with the actions that should be developed within the service, because without a guarantee of permanence, the professional can not make a plan that guarantees the continued assistance to the patient, which directly influences the relationship of trust between the professional and the population.